(untitled) (Argumentum, 2011)
The state, the family and the market are the main pillars of welfare regimes that have different configurations from one country to another. In Turkey, these mechanisms are under increasing pressure today. The family seems unable to extend protection beyond the nuclear household. In addition to that, support to rural employment and urban housing, deployed through clientele networks, decline. Wage insurance, as a way of accessing the social protection system, is also challenged by the characteristics of the labour market. We argue that the structure of employment is increasingly incompatible with the existing welfare system framework, which is mainly centred on formal workers insurance. In this context, will the current pensions and health reforms lead to a better articulation between employment forms and the social protection system? The first part of the article analyzes the evolution of the labour market since the 1990s. Recent adjustments of this market take place in the context of structural changes in the regulation of labour relations and of the economic model. The second part of the article examines social protection reforms. We analyse first parametric adjustments in the case of pensions (retirement age, period of contribution and replacement rates), and secondly, measures adopted to ensure universal access to health care and services. We argue that other forms of insurance and/or assistance might be necessary to increase the scope and depth of coverage. The last section explore three possible transformations of the Turkish welfare regime: increased labour market flexibility, a more important role of private insurance and the scope of social assistance mechanisms.